COVID 19 pandemic: Lesson learned by South Korea and its application with India’s perspective - Sinha, Smita; Chandra, Rishita (Indian Journal of Community Health, 2020)
A novel coronavirus named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in December 2019, in Wuhan city of Hubei province of China, which got transmitted throughout the nation and even world. It was declared as a Public Health Emergency by WHO on January 30th 2020, due to the increase in the number of cases reported from various regions of WHO with the evidence of human to human transmission. (1) Spread of COVID-19 across the globe: China reported first COVID-19 death on January 11th 2020. After a few weeks, 830 cases were diagnosed in China along with 26 reported deaths. By January 20, Wuhan was placed under lockdown and China alerted other nations about its spread in various provinces. (2) This contagious disease had spread to 24 nations outside China-Hong Kong-Macau, by 2nd February. About 172 countries and regions were engulfed by this virus by March 25, 2020. (3) Globally over 3,308,643 cases have been confirmed, over 234,123 deaths have been reported, and around 1,042,981 have recovered as on 30th April 2020. (4) Controlling the Pandemic COVID 19: success story of the Republic of Korea: Initially, one country which successfully stood out from the rest of the world was South Korea. The country confirmed its first few cases in late January and then reported a surge in the cases a few weeks later. The country was exploded with cases in dozens to hundreds to thousands during late February and early March and launched drive-through testing centers and massive contact tracing. Almost 909 new cases were identified in a single day of February 29th 2020 and was reported at peak. This data brought the country with 50 million population on the verge of a deluge. But the number of new cases was halved within a time period of just a week. The number of cases reduced to half within four days, and it halved, again the following day. (5)